ANALISIS PENGARUH PROGRAM KELUARGA HARAPAN (PKH) DAN PROGRAM CADANGAN BERAS PEMERINTAH (CBP) TERHADAP KESEJAHTERAAN KELUARGA PENERIMA MANFAAT (KPM): STUDI KASUS DI DESA LUBUK SOTING - Indriani, Sri Rahayu; Rahayu, Heffi Christya; Seprini, Seprini (Jurnal Daya Saing, 2025)
This study aims to analyze the influence of the Family Hope Program (PKH) and the Government Rice Reserve Program (CBP) on the welfare of beneficiary families (KPM) in Lubuk Soting Village. The research method used is a quantitative approach with multiple linear regression analysis techniques assisted by the SPSS program. The population in this study is all KPM recipients of PKH and CBP in Lubuk Soting Village, which totals 162 families. The research sample was taken using the purposive sampling method with the Slovin formula, so that 62 respondents were obtained. Data was collected through interviews and questionnaires distributed to KPM who were research respondents. The results showed that the T-count value for PKH reached 4,513 and for CBP was 4,239, both of which were greater than the T-table 2,001, which showed a positive and significant influence on the welfare of KPM. Simultaneously, the F test showed an F-count value of 29,485, greater than the F-table of 3.15, which indicates that PKH and CBP have a positive and significant effect together on the welfare of KPM. The average Respondent Achievement Level (TCR) for the welfare of KPM is 85.6%, which shows a very good category. Thus, the study concludes that both PKH and CBP significantly improve the welfare of KPM in Lubuk Soting Village, which includes meeting basic needs, access to education, and health. Keywords: Family Hope Program, Government Rice Reserve Program, welfare, Beneficiary Families.